2012
DOI: 10.1186/1471-2261-12-40
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cardiac rehabilitation on anxiety and depression in patients undergoing cardiac bypass graft surgery in Iran

Abstract: BackgroundMany patients experience anxiety and depression after cardiac bypass surgery.The aim of this study was to examine the effect of cardiac rehabilitation on anxiety and depression in patients undergoing coronary artery bypass grafting in hospitals affiliated to Shiraz University of Medical Sciences in southern Iran.MethodsFor this randomized controlled trial, 80 patients who met the inclusion criteria were recruited and randomly assigned to case and control groups. Anxiety was measured with the Spielber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 20 publications
4
61
3
1
Order By: Relevance
“…Além do mais, a ansiedade acarreta alterações fisiológicas, como taquicardia e hipertensão arterial, com consequente aumento do consumo de oxigênio e piora da evolução da doença (6)(7) . Assim, acredita-se que as alterações psicológicas podem e devem ser um dos focos de atenção do enfermeiro e diversas são as estratégias que podem ser utilizadas para redução da ansiedade, como, por exemplo, orientações individuais, orientações em grupo, orientações escritas, acolhimento do paciente, entre outras (8)(9)(10) . Diante do exposto, o objetivo do presente estudo foi comparar os sintomas de ansiedade entre pacientes em pré-operatório de cirurgia cardíaca que receberam acolhimento do enfermeiro ou do familiar, ou que não receberam nenhum tipo específico de acolhimento.…”
Section: Introductionunclassified
“…Além do mais, a ansiedade acarreta alterações fisiológicas, como taquicardia e hipertensão arterial, com consequente aumento do consumo de oxigênio e piora da evolução da doença (6)(7) . Assim, acredita-se que as alterações psicológicas podem e devem ser um dos focos de atenção do enfermeiro e diversas são as estratégias que podem ser utilizadas para redução da ansiedade, como, por exemplo, orientações individuais, orientações em grupo, orientações escritas, acolhimento do paciente, entre outras (8)(9)(10) . Diante do exposto, o objetivo do presente estudo foi comparar os sintomas de ansiedade entre pacientes em pré-operatório de cirurgia cardíaca que receberam acolhimento do enfermeiro ou do familiar, ou que não receberam nenhum tipo específico de acolhimento.…”
Section: Introductionunclassified
“…Kulcu et al (28) assessed the effect of cardiac rehabilitation on depression in patients with congestive heart failure and reported significant improvement in BDI scores in the treatment group in the short term. Sharif et al (29) observed significant decreases in BDI scores in 80 patients with CABG at the end of and 2 months after the 32 sessions of cardiac rehabilitation exercise program. However, in this study, we could not demonstrate improvement in the depression level of CABG after the 30 sessions of outpatient CRP.…”
mentioning
confidence: 99%
“…Nevertheless, the physiotherapeutic rehabilitation protocols have became necessary in the prevention of post-operatory complications [14].…”
mentioning
confidence: 99%
“…The benefits of inserting a post-operated patient in a cardiac rehabilitation (CR) program are well established [14] and physiotherapy is highlighted as a fundamental tool in the period of post cardiac surgery, acting from the evaluation of mechanical ventilation (MV) weaning, in the prevention of pulmonary complications, to the caring of patients' functional capacity. However, the treatment faces some restrictions due to pain, fear, insecurity and post-operatory unwillingness [15].…”
mentioning
confidence: 99%